Believers : does Australian Catholicism have a future? - Collins, Paul, 1940- (UNSW Press, 2008)
World Youth Day 08 and the visit of Pope Benedict XVI provide an opportunity to analyse the state of the Catholic Church in Australia. Believers does just that, offering a comprehensive account of everything that is right and wrong with Catholicism in Australia and asking whether it is really in decline. Paul Collins doesn?t shy away from the difficult questions that must be asked about the church: the lack of effective leadership, sexual abuse scandals, a drastic shortage of priests and declining mass attendance, particularly by young people. Believers delivers an optimistic message, bolstere.